Corporate entrepreneurship and organizational performance of small and medium enterprises in Malaysia: the role of innovation capability as the moderating factor / Joehary Sulaiman … [et al.] - Sulaiman, Joehary; Ngah, Rohana; Mohammad Syah, Khairul Anuar; Ab. Kadir, Ahmad Rusydan (2018)
Small and Medium Enterprises (SMEs) have been an integral part of Malaysia’s economic transformation process. This transformation process is linked with the performance of SMEs. Performance of SMEs can be viewed from the corporate entrepreneurship perspective and the innovation capability as the moderating factor driving SME performance. Corporate entrepreneurship has become a necessary precondition for sustainable business development as the main measurement of superior organizational performance innovation capability is also linked to organizational performance by constantly initiating the capability of the organization to transform information and availability resources as well as new concepts into products, services, systems and processes for the benefit of the firm and its stakeholders. Therefore, the focus of this paper is to explore the SMEs performance in Malaysia from the corporate entrepreneurship perspectives and the relevance of innovation capability as a moderator in the organizational performance. A research framework will be suggested to be used to explore and test the relationships between corporate entrepreneurship, innovation capability and organizational performance.